Characteristics of Hepatocellular Carcinoma Aggressiveness Factors in Turkish Patients - Akkiz, Hikmet; Carr, Brian I.; Yalcin, Kendal K.; Guerra, Vito; Kuran, Sedef; Altintas, Engin; Doran, Figen (Karger, 2018)
A large cohort of hepatocellular carcinoma (HCC) patients from several collaborating Turkish institutions were examined for the tumor parameters of maximum diameter (MTD), portal vein thrombosis (PVT), and alpha-fetoprotein (AFP) levels. A relationship was found between MTD and blood platelet levels. Patients with large >= 5 cm tumors who had normal platelet levels had significantly larger tumors, higher percent of PVT, and significantly lower blood total bilirubin and liver cirrhosis than similar >= 5 cm tumor patients having thrombocytopenia. A comparison of patients with and without PVT showed significantly larger tumors, greater multifocality, blood AFP, and C-reactive protein levels, and, interestingly, lower HDL levels in the patients with PVT. Fifty-eight percent of the total cohort had AFP levels <= 100 IU/mL ( and 42.1% had values <= 20 IU/mL). These patients had significantly smaller tumors, less tumor multifocality and percent PVT, lower total bilirubin, and less cirrhosis. There was considerable geographic heterogeneity within Turkey in the patterns of HCC presentation, with areas of higher and lower hepatitis B virus, hepatitis D virus, cirrhosis, and tumor aggressiveness parameters. Turkish patients thus have distinct patterns of presentation, but the biological relationships between MTD and both platelets and bilirubin levels are similar to the relationships that have been reported in other ethnic patient groups. (C) 2017 S. Karger AG, Basel
Keywords: Albumin; Hepatocellular carcinoma; Turkey; alpha-Fetoprotein; Tumor mass; Aggressiveness